PROSEDUR PEREKRUTAN VOLUNTEER EVENT PADA PT. DYANDRA PROMOSINDO - Maharani (Jurnal Manajemen dan Profesional, 2024)
The task of this study discusses Volunteer Recruitment Procedures of PT. Dyandra Promosindo’s Event. The method used by the author on this study is qualitative method with secondary data collection technique and doing direct observation in the field, and interview. The observation result shows the Volunteer Recruitment Procedures of PT. Dyandra Promosindo’s Event consists of the stages of determining the needs of the workforce, then conducting socialization, filling in digital forms. Interviews, database compilation, and ending with a volunteer meeting and signing of employment contracts or Memorandum of Understanding (MoU).